Janice VanCleave's Science around the world : activities on biomes from pole to pole - VanCleave, Janice Pratt, 1942- (Wiley, 2004)
"Presents interesting facts and fun experiments that relate to different geographical regions of the world--also known as biomes."--Zadní s. obálky
Terminologický slovník
Keywords: biomy; přírodovědné vzdělávání; pokusy; biomes; science education; experiments; publikace pro děti; children's literature